TRANSFORMATIONS OF DARWIN'S THOUGHT IN CAPE HORN: A LEGACY FOR SCIENCE AND ENVIRONMENTAL ETHICS - Rozzi Marin, Ricardo Roberto (My University, 2018)
During his expeditions through the archipelagos in the Cape Horn region, Charles Darwin was surprised by the presence of humans in Cape Horn. His observations on the landscapes, the fauna, and the life habits of the Fuegian people led him to question Victorian concepts, and stimulated his initial thoughts about the theory of evolution, including the human species. The evolutionary thought of Darwin on the human species began to take shape in Cape Horn. In this paper, I examine how in the course of his life Darwin transformed his initial judgments about the Fuegian people, and how this change of judgment is associated with the maturation of his concepts to forge the theory of human evolution. I also examine his early reflections on an ecological-contextual concept of good living, and the ethical implications that derive from his theory of human evolution. From the identification of these concepts, I analyze the implications for a scientific thought and for an environmental ethics that may contribute to address some of the ultimate causes of the current global socio-environmental crisis. In the context of this special issue of Magallania, this analysis offers a theoretical explanation of the name of the international course in Field Environmental Philosophy, which is also called "Tracing Darwin's Path in Cape Horn," offered annually since 2005 by the University of Magallanes and the University of North Texas University in the Cape Horn Biosphere Reserve.
Keywords: good life; fuegians; human evolution; post-truth; yahgan